Patterns, Receptors, and Signals: Regulation of Phagosome Maturation. Issue 6 (June 2017) - Pauwels, Anne-Marie; Trost, Matthias; Beyaert, Rudi; Hoffmann, Eik
Abstract : Recognition of microbial pathogens and dead cells and their phagocytic uptake by specialized immune cells are essential to maintain host homeostasis. Phagosomes undergo fusion and fission events with endosomal and lysosomal compartments, a process called 'phagosome maturation', which leads to the degradation of the phagosomal content. However, many phagocytic cells also act as antigen-presenting cells and must balance degradation and peptide preservation. Emerging evidence indicates that receptor engagement by phagosomal cargo, as well as inflammatory mediators and cellular activation affect many aspects of phagosome maturation. Unsurprisingly, pathogens have developed strategies to hijack this machinery, thereby interfering with host immunity. Here, we highlight progress in this field, summarize findings on the impact of immune signals, and discuss consequences for pathogen elimination. Trends: Self and non-self immune signals are able to delay or accelerate phagosome maturation, and their effects are dependent on the phagocytic cell type, duration of stimulation, and whether the stimulus is particle bound or present in the cellular environment. Acceleration of phagosome maturation enhances pathogen killing, while a delay in phagosome maturation preserves antigenic peptides for presentation to T cells and to initiate adaptive immune responses. Besides its functions in pathogen killing and antigen presentation, the phagosome also functions as a signaling platform and interacts with other cell organelles. Some pathogens are able to arrest phagosome maturation to enhance their intraphagosomal survival and replication or to promote phagosomal escape. The latex bead phagocytosis model system combined with mass spectrometry is a powerful technique to analyze changes in the phagosomal proteome.